2017
DOI: 10.1038/ncb3512
|View full text |Cite
|
Sign up to set email alerts
|

Shh-mediated centrosomal recruitment of PKA promotes symmetric proliferative neuroepithelial cell division

Abstract: Tight control of the balance between self-expanding symmetric and self-renewing asymmetric neural progenitor divisions is crucial to regulate the number of cells in the developing central nervous system. We recently demonstrated that Sonic hedgehog (Shh) signalling is required for the expansion of motor neuron progenitors by maintaining symmetric divisions. Here we show that activation of Shh/Gli signalling in dividing neuroepithelial cells controls the symmetric recruitment of PKA to the centrosomes that nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
69
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(74 citation statements)
references
References 59 publications
5
69
0
Order By: Relevance
“…Localisation of PKA to the centrosome is thought to block the PKA kinase activity, shifting the balance towards more activated Gli (Barzi et al, 2010, Saade et al, 2017. In a recent study, PKA was found symmetrically localised to both mitotic centrosomes in the early chick neuroepithelium where divisions are almost exclusively proliferative (Saade et al, 2017). At later stages, when asymmetric divisions predominate, PKA appeared asymmetrically localised, with high levels in only one centrosome (Fig.…”
Section: Regulation Of Sonic Hedgehog Signalling Via the Centrosomementioning
confidence: 99%
See 4 more Smart Citations
“…Localisation of PKA to the centrosome is thought to block the PKA kinase activity, shifting the balance towards more activated Gli (Barzi et al, 2010, Saade et al, 2017. In a recent study, PKA was found symmetrically localised to both mitotic centrosomes in the early chick neuroepithelium where divisions are almost exclusively proliferative (Saade et al, 2017). At later stages, when asymmetric divisions predominate, PKA appeared asymmetrically localised, with high levels in only one centrosome (Fig.…”
Section: Regulation Of Sonic Hedgehog Signalling Via the Centrosomementioning
confidence: 99%
“…Protein kinase A (PKA) also plays a role in regulating Gli activity by phosphorylating Gli proteins at 6 sites, rendering them inactive (Niewiadomski et al, 2014). Localisation of PKA to the centrosome is thought to block the PKA kinase activity, shifting the balance towards more activated Gli (Barzi et al, 2010, Saade et al, 2017. In a recent study, PKA was found symmetrically localised to both mitotic centrosomes in the early chick neuroepithelium where divisions are almost exclusively proliferative (Saade et al, 2017).…”
Section: Regulation Of Sonic Hedgehog Signalling Via the Centrosomementioning
confidence: 99%
See 3 more Smart Citations